The Effect of ZISWAF, BOPO, and Non-Operating Profit/Loss Receipts on Reserve Requirements with Firm Size as a Moderating Variable for the 2015.Q1 – 2023.Q3 Perioda - Afrizal, Nova Maulana; Budianto, Eka Wahyu (Fakultas Ekonomi dan Bisnis Islam, 2024)
The research examines the influence of ZISWAF funds acceptance, BOPO, and non-operational profit/loss on GWM in Islamic banks in Indonesia, with firm size as a moderating variable. ZISWAF funds contribute to the growth of the Islamic economy, BOPO measures operational efficiency, and non-operational profit/loss involves income or expenses outside main operations. Using panel data regression with a Fixed Effect Model, the study finds that the independent variables do not significantly affect GWM. The coefficient of determination shows that 16.56% of company value is explained by institutional ownership and capital structure. Methodology includes Chow, Hausman, or LM tests, and classic assumption tests like normality, multicollinearity, and heteroskedasticity. Liquidity management strategies are influenced by BOPO, non-operational profit/loss, and ZISWAF funds, impacting GWM policy. The effects of these variables on GWM can be moderated by company size, as revealed through Panel Data Regression and Moderated Regression Analysis (MRA).